Effects of Gibberellic Acid (GA3) Application on The Plant Growth and Seed Production of Pinto Peanut (Arachis pintoi Krap & Greg) - Dani, Robi Rahmat; Kartika, Juang Gema; Sari, Maryati (Department of Agronomy and Horticulture, IPB University, 2023)
Pinto peanut (Arachis pintoi Krap & Greg.) is a legume that is usually used as a cover crop, bio mulch in fruit and vegetable plantations, ornamental plants, and animal feed. Pinto peanut has many benefits; through the symbiosis with rhizobacteria they can fix nitrogen, as ground cover can reduce the risk of landslides, inhibit weed growths, and is a source of nectar for bees. Arahcnis pintoi can be propagated vegetatively or generatively, but generative propagation is hard to conduct in the tropics because it takes a long time for the plants to produce seeds. Our study was conducted to determine the effect of GA3 application on seed production of A. pintoi. The experiment was arranged in a single factor randomized complete block design with GA3 concentration of 0, 75, 150, 225, and 300 ppm. An orthogonal polynomial test was conducted to determine the effective concentrations for GA3 on seed formation and seed viability. Harvested seeds were stored for 1 month, then sown on sand medium; the seeds were soaked in 1% KNO3 solution to break seed dormancy prior. Our study showed that the GA3 effective concentration range from 130.69 ppm to 137.16 ppm, indicated by the increase the number of flowers at 105, 120, 135, and 150 DAT up to 28.59% compared to control. GA3 at 126.80 ppm can also increase the number of harvested pods by 18.16%. The effect of GA3 on vegetative growth was shown by the increase in the growth of new individual plants concentration, i.e. 53.25 new individual plant with GA3 application of 141.88 ppm.